PSXI-33 Differential Action of TGR5 Agonists on GLP-2. (7th December 2018) - Lin, S; Stoll, B; Robinson, J; Pastor, J; Cruz, S; Lau, P; Marini, J; Ipharraguerre, I; Hartmann, B; Holst, J; Olutoye, O; Fang, Z; et al.
Abstract: We previously showed that feeding bile acids could induce glucagon-like peptide 2 (GLP-2) secretion and intestinal growth in parenteral nutrition-fed (PN) piglets. We hypothesize that bile acids function as agonist for the G protein-coupled bile acid receptor 1 (TGR5) expressed in enteroendocrine L cells to induce GLP-2 secretion. Our aim in this study was to test whether natural orally administered TGR5 agonists could increase GLP-2 secretion and intestinal adaptation in a piglet short bowel model. In study 1, twenty-four, neonatal piglets were PN-fed and gavaged with one of two TGR5 (ursolic acid (UA) and compound R071) treatments to measure acute GLP-2 secretion. In study 2, neonatal piglets underwent either 80% midjejunoileal resection alone or transection and reanastomosis with no resection (sham). Four treatments were studied: 1) transection, 2) resection, 3) resection + 10 mg UA, 4) resection + 60 mg R071. In study 1, oral gavage with UA, but not R071, increased (P < 0.05) GLP-2 secretion. In study 2, compared to transection, remnant ileum villus height, crypt cell proliferation, and plasma GLP-2 secretion were increased (P < 0.05) by resection, but not further stimulated by UA or R071. Bile acid profiling showed that UA and R071 increased (P < 0.05) conjugated HCA and HDCA concentration in liver and decreased (P < 0.05) conjugated HCA, HDCA and CDCA concentration in ileum. Resection tended (P = 0.08) to increase, while UA decreased (P < 0.05) liver IL-1β gene expression. We conclude that oral TGR5 agonists differentially increased GLP-2 secretion in healthy PN-fed pigs, but did not augment GLP-2 secretion or intestinal adaptation after resection in short-bowel piglets. We found that TGR5 agonists altered bile acid homeostasis and had anti-inflammatory actions in liver in short-bowel piglets.